Removal of trihalomethanes in synthetic waters by adsorption on activated carbon - Franco, Elton Santos; Aguilar, Núbia Aparecida de; Costa, Alexandre Sylvio Vieira da; Souza, Márcio Coutinho de; Rodrigues, Jairo Lisboa; Braga , Nathalia Oliveira (National Journal of City Management, 2024)
The present study aimed to evaluate the efficiency of granular activated carbon for removing trihalomethanes (TAM) in synthetic waters. To detect and quantify the TAM, the method used was liquid-liquid extraction associated with gas chromatography coupled mass spectrometry. Samples with concentrations of 100 and 150 μg.L-1 were prepared at a laboratory scale, the first being the maximum value allowed by Ordinance No. 888 of May 4, 2021, of the Ministry of Health. The results were satisfactory, with an average of up to 87% TAM removal, proving that filtration with granular activated carbon is eficiente as a low-cost technique in homes.